Het Geheim China : Lineart/09 gids voor de kunstverzamelaar - Derycke, Luc; Mels, Mieke (Gent : Lineart vzw Gent, 2009)
Delvoye, Wim ; Uytterhaegen, Frank ; Weiwei, Ai
Schenking Lineart
boek
Keywords: China